OPTIMIZATION OF CLAY MASK FORMULA FROM LEAF SI KEJUT (Mimosa pudica L.) EXRACT USING SIMPLEX LATTICE DESIGN METHOD - Fitriawati, Anna; Rahmatillah, Annie; Agustiningrum, Nurul (LPPM Universitas Duta Bangsa Surakarta, 2025)
Clay mask is a facial mask used to remove dirt and blackheads from the skin. It is particularly suitable for acne-prone skin, as clay masks provide a refreshing sensation, absorb excess oil, and help manage blackheads. Mimosa pudica, commonly known as the